2010
DOI: 10.1038/labinvest.2010.57
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of HOXD3 as a marker of prostate cancer progression

Abstract: DNA methylation in gene promoters causes gene silencing and is a common event in cancer development and progression. The ability of aberrant methylation events to serve as diagnostic and prognostic markers is being appreciated for many cancers, including prostate cancer. Using quantitative MethyLight technology, we evaluated the relationship between HOXD3 methylation and clinicopathological parameters including biochemical recurrence, pathological stage, Gleason score (GS), and Gleason pattern in a series of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 46 publications
4
61
0
Order By: Relevance
“…Aberrations to DNA methylation in certain GP morphologies require further investigation as it may improve personalized patient treatment by utilizing biomarker information. The DNA methylation of APC, CYP26A1, HOXD3, HOXD8, RASSF1, TBX15 and TGFβ2 genes were investigated in the current study, as they have previously been revealed as promising prognostic biomarkers for PCa with the potential for clinical utility in independent patient cohorts (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Aberrations to DNA methylation in certain GP morphologies require further investigation as it may improve personalized patient treatment by utilizing biomarker information. The DNA methylation of APC, CYP26A1, HOXD3, HOXD8, RASSF1, TBX15 and TGFβ2 genes were investigated in the current study, as they have previously been revealed as promising prognostic biomarkers for PCa with the potential for clinical utility in independent patient cohorts (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from 10 µm sections of previously prepared FFPE blocks matching the selected H&E slides using a QIAamp DNA Mini kit (Qiagen, Inc., Valencia, CA, USA), as previously described (23)(24)(25). DNA methylation was analyzed in the same GP4 area used for histological evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations